MiR‐449a exerts tumor‐suppressive functions in human glioblastoma by targeting Myc‐associated zinc‐finger protein. Issue 3 (20th November 2014) - Yao, Yilong; Ma, Jun; Xue, Yixue; Wang, Ping; Li, Zhen; Li, Zhiqing; Hu, Yi; Shang, Xiuli; Liu, Yunhui
Abstract : Glioblastoma (GBM) is one of the most common and aggressive primary brain tumors in adults. Deregulated expression of microRNAs (miRNAs) has been associated with GBM progression through alterations in either oncogenic or tumor suppressor targets. Here, we elucidated the function and the possible molecular mechanisms of miR‐449a in human GBM cell lines and tumor specimens‐derived glioblastoma stem cells (GSCs). Quantitative real‐time PCR demonstrated that miR‐449a was down‐regulated in human GBM cell lines and GSCs. Functionally, miR‐449a acted as a tumor suppressor by reducing cell proliferation, migration and invasion as well as inducing apoptosis in human GBM cell lines and GSCs. Myc‐associated zinc‐finger protein (MAZ) was identified as a direct target of miR‐449a, mediating these tumor‐suppressive effects, demonstrated by Western blot assay and luciferase assays. Moreover, over‐expression of miR‐449a inhibited the expression of Podoplanin (PDPN) by down‐regulating MAZ which could positively control the promoter activities via binding to the promoter of PDPN, demonstrated by luciferase assays and chromatin immunoprecipitation assays. Further, the PI3K/AKT pathway was blocked when MAZ was down‐regulated by miR‐449a. This process was coincided with the up‐regulation of apoptotic proteins and the down‐regulation of anti‐apoptotic proteins, MMP2 and MMP9. Furthermore, nude mice carrying over‐expressed miR‐449a combined with knockdown MAZ tumors produced the smallest tumors and the highest survival. These results elucidated a novel molecular mechanism of GBM progression, and may thus suggest a promising application for GBM treatment. Highlights: MiR‐449a expression was down‐regulated in human GBM cell lines and GSCs. MiR‐449a reduced proliferation, migration and invasion, and induced apoptosis. MAZ was identified as a direct target of miR‐449a. MAZ up‐regulated the promoter activities and bound to the PDPN promoters. The mechanisms were the down‐regulation of PI3K/AKT pathway and PDPN expression.